What Explains Big Gender Disparities in India? Local Industrial Structures and Female Entrepreneurship - Ghani, Ejaz; Kerr, William R.; O'Connell, Stephen D. (World Bank, Washington, DC, 2013)
Despite rapid economic growth, gender disparities in women's economic participation have remained deep and persistent in India. What explains these huge gender disparities? Is it poor infrastructure, limited education, and gender composition of the labor force and industries? Or is it deficiencies in social and business networks and a low share of incumbent female entrepreneurs?This paper analyzes the spatial determinants of female entrepreneurship in India in the manufacturing and services sectors. Good infrastructure and education predict higher female entry shares. There are strong agglomeration economies in both manufacturing and services, where higher female ownership among incumbent businesses within a district-industry predicts a greater share of subsequent entrepreneurs will be female. Moreover, higher female ownership of local businesses in related industries (similar labor needs, input-output markets) predicts greater relative female entry rates. Gender networks thus clearly matter for women's economic participation. However, there is a need to develop a better understanding of how gender networks influence aggregate efficiency. There is no doubt that gender empowerment can be the escalator to realizing human potential and for creating a robust platform for growth and job creation.